Familial Mediterranean fever gene (MEFV) mutations and disease severity in systemic lupus erythematosus (SLE): implications for the role of the E148Q MEFV allele in inflammation. (June 2015) - Deniz, R; Ozen, G; Yilmaz-Oner, S; Alibaz-Oner, F; Erzik, C; Aydin, S Z; Inanc, N; Eren, F; Bayalan, F; Direskeneli, H; Atagunduz, P
Objective: Observed low prevalence of SLE among familial Mediterranean fever (FMF) patients in several large cohorts suggests a possible protective effect of the MEFV mutations from SLE. In contrast, SLE patient carriers for the common MEFV mutations had rather complex disease expression with an increased frequency of febrile episodes and pleurisy and a decreased renal complication rate. Our aim was to investigate the prevalence of MEFV gene mutations in patients with SLE and their effect on organ involvement in a well-defined group of biopsy-proven SLE nephritis patients. Material and method: The prevalence of four MEFV gene mutations (M694V, M680I, V726A and E148Q) was investigated in 114 SLE patients and effect on disease severity was analyzed in patients with biopsy-proven SLE nephritis. Results: None of the SLE patients fulfilled the revised Tel-Hashomer criteria. Fourteen of 114 SLE patients (12.2%) were found to carry at least one MEFV mutation. A single patient in the SLE-Nephritis group was compound heterozygous for M694V/M680I mutations and only one patient in the SLE-Mild group was homozygous for E148Q mutation. Carrier frequency was similar to controls in SLE patients (12.2 vs 18.8%, p = 0.34). After the exclusion of the less penetrant E148Q mutation, re-analysis revealed an association between exon 10 mutations and SLE nephritis ( p = 0.050, odds ratio (OR) = 4.16, 95% confidence interval (CI) = 1.04–16.6). Carrier rate for the E148Q mutation decreased in the SLE group (controls vs. SLE = 20/186 vs. 3/114, p = 0.08) and E148Q mutation was absent in SLE nephritis (controls vs. SLE nephritis = 20/186 vs. 0/47, p = 0.016, OR = 11.69, 95% CI = 0.69–197.13). Conclusions: Carrier rate for the studied MEFV mutations was slightly lower in the SLE group, which is in agreement with previous observations that FMF may confer some protection from SLE. Exon 10 mutations were associated with SLE nephritis after the exclusion of the E148Q mutation. The significance of the E148Q as a disease-causing mutation is controversial, and whether E148Q substitution is a polymorphism generally affecting inflammatory pathways is not addressed in the current literature. In this regard, absence of the E148Q mutation in SLE nephritis may serve as a clue for further investigation into its role as a general modulatory polymorphism for inflammation. This clarification is necessary to conclude whether other more penetrant MEFV gene mutations confer susceptibility to nephritis in SLE.